Pembentukan Karakter melalui Profesionalisme Guru Pendidikan Agama Kristen dalam Kurikulum Merdeka - Tapilaha, Sandra Rosiana (STT Pelita Dunia, 2024)
Abstract: The purpose of this article is to examine the significance of the role of Christian religious education in shaping the character of students or learners, especially in the midst of the turbulent dynamics of the times. In the era of the Merdeka Curriculum, which emphasizes student empowerment and individual potential development, the professionalism of Christian religious education teachers is an important factor influencing character building. This research uses a qualitative method with a descriptive approach. The researcher reviewed and interpreted various related literature to refer to the results and conclusions. This study revealed the results that the identity and role of the teacher in the learning process is very important, with reference to his creativity, innovation, professionalism in education that has an impact on the character building of students, through the actions of conveying Christian teachings, building good relationships, providing emotional support, being a positive role model. This research also provides an important contribution for educational institutions to train and support Christian religious education teachers in developing professionalism to maximize their influence in shaping learners’ character.